Effect of Alcohol Disinfection on the Handle and Blade of Vegetables Knives by using ATP Inspection and Microbial Stamp Test (Global Journal of Medical Research, 2020)
To prevent food poisoning, we focused on kitchen vegetable knives, which are likely to cause secondary contamination, and conducted hygiene inspections to obtain results. The values after cooking and after washing, and after washing and after 70%spraying alcohol compared using the ATP wiping test and the microbial stamp test (selective medium: general bacteria, Escherichia coli, Staphylococcus aureus, Salmonella, Vibrio parahaemolyticus). As a result, the ATP test value decreased statistically significantly and became 100 or less after 70%alcohol sprayings. However, not all of the bacterial counts in the selective medium were statistically significantly different even after 70%alcohol sprayings. The reason the data was not clear due to 70% alcohol spray conditions. It may be advisable to perform a microbiological stamp test after applying 70%alcohol spray multiple times instead of once to a fully moistened knife handle and blade. In the future, we would like to consider the handling of more hygienic cooking utensils by further changing the 70%alcohol spraying conditions and conducting, Microbiological tests using a selective medium.
Keywords: ATP test; microbial stamp test; the handle of the knife; the blade of the knife; alcohol disinfection